Reversal of neurovascular coupling in the default mode network: Evidence from hypoxia. Issue 4 (April 2021) - Rossetti, Gabriella MK; d'Avossa, Giovanni; Rogan, Matthew; Macdonald, Jamie H; Oliver, Samuel J; Mullins, Paul G
Local changes in cerebral blood flow are thought to match changes in neuronal activity, a phenomenon termed neurovascular coupling. Hypoxia increases global resting cerebral blood flow, but regional cerebral blood flow (rCBF) changes are non-uniform. Hypoxia decreases baseline rCBF to the default mode network (DMN), which could reflect either decreased neuronal activity or altered neurovascular coupling. To distinguish between these hypotheses, we characterized the effects of hypoxia on baseline rCBF, task performance, and the hemodynamic (BOLD) response to task activity. During hypoxia, baseline CBF increased across most of the brain, but decreased in DMN regions. Performance on memory recall and motion detection tasks was not diminished, suggesting task-relevant neuronal activity was unaffected. Hypoxia reversed both positive and negative task-evoked BOLD responses in the DMN, suggesting hypoxia reverses neurovascular coupling in the DMN of healthy adults. The reversal of the BOLD response was specific to the DMN. Hypoxia produced modest increases in activations in the visual attention network (VAN) during the motion detection task, and had no effect on activations in the visual cortex during visual stimulation. This regional specificity may be particularly pertinent to clinical populations characterized by hypoxemia and may enhance understanding of regional specificity in neurodegenerative disease pathology.